From the beaker to the body: translational challenges for electrochemical, aptamer-based sensors. Issue 10 (20th February 2020) - Arroyo-Currás, Netzahualcoyotl; Dauphin-Ducharme, Philippe; Scida, Karen; Chávez, Jorge L.
Abstract : The ultimate goal of implantable electrochemical, aptamer-based (E-AB) sensors is to enable the continuous and precise monitoring of clinically and physiologically important targets in the body for prolonged periods. Abstract : The ultimate goal of implantable bioanalytical sensors is to enable the continuous and precise monitoring of clinically and physiologically important targets in the body for prolonged periods. Electrochemical, aptamer-based (E-AB) sensors already achieve this goal in a modular way, so far allowing the multihour in vivo monitoring of over half a dozen molecular targets without relying on their specific chemical reactivities. E-AB sensors achieve this modularity by employing nucleic acid aptamers as recognition elements, which can reversibly and selectively bind to molecular targets even in complex biological fluids such as unprocessed blood. However, the translation of the E-AB platform from bench-top, in vitro proof-of-concept demonstrations to truly relevant in vivo clinical applications still faces challenges, some of which are dependent on innovations in the fields of material sciences, interfacial chemistry, biomedical engineering and data management. In this review we critically discuss some of the challenges that the E-AB platform still needs to overcome before it can achieve full, unhindered translation to biomedical and clinical research, decentralized diagnostics and medical applications.